: Program “CAHAYA TBC” (Curahan Hati Yang Sakit TBC) - Rohana, I Gusti Ayu Putu Desy; Saprianto, Saprianto; Hasan Martadinata, Umar; Zanzibar, Zanzibar (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Tuberculosis (TB) is an infectious disease that causes the second death after the Human Immunodificiency Virus. Compliance with TB treatment is very important to achieve the Millennium Development Goals (MDGs) in the context of eliminating TB. Health problems in OKU Regency note that TB is the 10th type of infectious disease with the highest incidence rate. The partner's problem from the results of the preliminary study is that the provision of TB treatment services, strengthening the motivation of Drug Swallowing Supervisors (PMO), and providing information/education is not yet optimal. The solution implemented by the service team is the implementation of the "CAHAYA TBC Program", which is a village development and innovation program consisting of 4 activity sessions, and involving patients, PMO, health cadres, and those responsible for the Puskesmas TB program. Patient compliance in undergoing the treatment program will be monitored in the "TB Patient Self-Management Guidance Module" module which will be carried out for 3 months and involve 30 people. The results of implementing the program were an increase in knowledge by 47%, an increase in skills by 22.5% from the pre and post test results of participants, and an increase in TB treatment visits to the Tanjung Agung Community Health Center UPTD by 92% at the end of the activity.